ANALISIS PENGARUH IKLAN ONLINE TERHADAP MINAT BELI: STUDI KASUS PENGGUNA APLIKASI E-COMMERCE DI OKU TIMUR - Margahana, Helisia Margahana (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to determine the effect of online advertising on buying interest in consumers who use e-commerce media in the Eastern OKU region. Design/methodology/approach- Data were collected through a questionnaire, as many as 100 respondents were chosen randomly. Linear regression is used to test the stud hypothesis. Findings- The results show that online advertising does not affect purchasing interest. This condition indicates that consumers are now getting smarter and have broad preferences to determine purchases intention. Implications- this study can provide information to marketers to pay attention to online advertising content so that it can appeal to prospective buyers. Keywords: online advertising, purchase intention